Institutional Development and Colonial Heritage within Brazil - Joana Naritomi; Rodrigo R. Soares; Juliano J. Assunç\~ao (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2009)
This paper analyzes the determinants of local institutions and distribution of political power within a constant `macro-institutional' setting. We show that characteristics of Brazilian municipalities related to institutional quality and distribution of political power are partly inherited from the colonial histories experienced by different areas of the country. Municipalities with origins tracing back to the sugar-cane colonial cycle – characterized by a polarized and oligarchic socioeconomic structure – display today more inequality in the distribution of endowments (land). Municipalities with origins tracing back to the gold colonial cycle – characterized by a heavily inefficient presence of the Portuguese state – display today worse governance practices and less access to justice. The colonial rent-seeking episodes are also correlated with lower provision of public goods and lower income per capita.
Keywords: 330; institutions; colonial heritage; rent-seeking; geography; Brazil JEL Codes: N26; O17; O40; Kommunalverwaltung; Rent-Seeking; Politisches System; Institutionenökonomik; Kolonialismus; Räumliche Verteilung; Brasilien